Implementation Of Problem Credit Debtaccording To Civil Law - Ashar Sinilele (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2021)
The policy of implementing haircuts at the Bank has accelerated the restructuring of small and medium business loans. The issuance of these two decrees and the imposition of haircuts in theworld bankingfor certain parties have caused a legal problem, namely a decree has set aside all the rules stipulated in the existing laws, for example the rules regarding contract law. in the Civil Code. This is a deviation from the applicable legal principle, namely that higher regulations override lower regulations. Based on experience to achieve the expected effectiveness, it is better if thepolicy haircut through a presidential decree does not only provide discounts on bad loans but also does not limit the time interval for the loss, the important thing is that the debtor's criteria meet the requirements of SMEs affected by the monetary crisis.Keywords: Debt Cutting, Credit, Civil Law